Triangle inequality for subtraction? [duplicate]

Why is $$|a - b| \geq|a| - |b|$$?

• it would be also nice to see an intuitive explanation/answer to this. It feels it should be obvious, no? Nov 2, 2017 at 2:40
• Does this answer your question? Reverse Triangle Inequality Proof Feb 25, 2020 at 7:14

It's sometimes called the reverse triangle inequality. The proper form is $$\left| a - b \right| \ge \big||a| - |b|\big|$$ For the proof, consider $$|a| = |a - b + b| \le |a - b| + |b|$$ $$|b| = |b - a + a| \le |a - b| + |a|$$ so that we have $$-|a-b|\le|a|-|b| \le |a - b|$$

• Let $s_n$ be a sequence. Is this valid then: $|s_n - s| < 1 \iff ||s_n| - |s|| < 1 \iff |s_n| < |s| + 1$? Oct 15, 2012 at 4:08
• That is indeed valid. You don't even need the reverse triangle inequality. $$|s_n| = |s_n - s + s| \le |s_n -s | + |s| < |s| + 1$$
– EuYu
Oct 15, 2012 at 4:10
• @SPRajagopal The only property we used in the proof was the triangle inequality itself, so this holds with any norm.
– EuYu
Oct 8, 2014 at 14:05
• is there an intuitive explanation for why this is true? Nov 2, 2017 at 2:37
• @CharlieParker It depends on what you mean by intuitive. The statement is a formalization of the fact that "the difference of two sides of a triangle is always less than (or equal to) the third side". I don't know if you find that fact intuitive or not, but it is just a restatement of the fact that "the sum of two sides of a triangle is always greater (or equal to) the third side", which is the triangle inequality itself. This is of course reflected in the fact that the reverse triangle inequality is a direct consequence of the triangle inequality.
– EuYu
Nov 2, 2017 at 13:10

No. For example, $|(-2)-3|=5>|-2|-|3|=-1.$

I think you're thinking of $||a|-|b||\le |a- b|.$

The length of any side of a triangle is greater than the absolute difference of the lengths of the other two sides:

$$||a|-|b||\leq |a-b|$$

Here is a proof:

$$|a+(b-a)|\leq |a|+|b-a|$$

and,

(1) $$|a-b|\geq |a|-|b|$$

Interchanging $a$ and $b$, we get also

(2) $$|a-b|\geq |b|-|a|$$

Combining (1) and (2) we get our desired result.